THE COSTUME DESIGNSN FOR THE MORLAMWATKHONKAEN'S DANCERS - Trairatrangsee, Wasan; Chantamala, Orarom (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2023)
This research aimed to study Mor Lam Ward KhonKaen dancers' costume development as well as the dancers' costume design by using a qualitative research method. The data was collected through documents and field data of a sample group of 47 people, which included 9 experts, 18 practitioners, and 20 general people. Observation forms and interview forms were used as research instruments. The research results were presented by descriptive and analytical methods. data analysis was presented using the descriptive analysis approach. The results of the study found that 1. Mor Lam Ward KhonKaen dancers' costume development from the past to the year 2019 can be divided into 3 periods, each of which has its development and invention transfer process including getting ideas from outside to combine all the time, such as the idea of ​​modifying the production of costumes to respond to social phenomena and to stimulate stability and survival in accordance with the changing social trends in each era especially in a society that is constantly moving and there is a high competition in business 2. As for the costume design of the Khon Mor Lam Ward KhonKaen dancers, there is a paradigm in creating works through design concepts that are primarily in accordance with popular trends by replicating the dancers' costumes in various entertainment venues and media, integrating with the designer's creativity and experience under the concept of two primary groups: 1) a band that performs music. 2) Country and Mo Lam genres, which are separated into six categories based on costume style: 1) shirt, 2) skirt, 3) pants, 4) sarong, 5) loincloth, and 6) ready-made costume.